Demographic Characteristics and the Performance of Supervisors of Swallowing Drugs in Parepare, Indonesia - Syarifuddin, Syarifuddin; Wahyuni, Chatarina Umbul; Melania, Soenarnatalina (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
-